Transferrin variation and evolution of Canadian barren-ground caribou - Røed, Knut H.; Thomas, D. C. (Rangifer, 1990)
Blood samples were obtained from 95 barren-ground caribou (Rangifer tarandus groenlandicus) of the Beverly herd in Northwest Territories, Canada. Polyacrylamid gel electrophoresis was used to score for genetic variation in the locus coding for transferrin. The pattern of allele frequency distribution are compared with previously reported values of Eurasian tundra reindeer (R.t. tarandus), Alaska caribou (R.t. granti), Peary caribou (R.t. pearyi), and Svalbard reindeer (R.t. platyrhynchus). In the Beverly herd a total of 21 different transferrin alleles were detected. The amount of genetic variation was higher in the Canadian barren-ground caribou than what has been detected in other subspecies of reindeer/caribou. Highly gene-tical differences in the allele frequencies were detected between the Canadian barren-ground caribou and the other subspecies. The genetic identity analyses indicates approximately the same amount of genetic differentiation when the Canadian barren-ground caribou are compared with Alaska caribou as with the Peary caribou. The allele frequency pattern could be explained by a possible origin of the Canadian barren-ground caribou from an ancestral population which was genetical influenced by animals surviving the We-ichselian glaciation in refugia both in high Arctic, in Beringia, and south of the ice sheet.